PENERAPAN PRINSIP PIERCING THE CORPORATE VEIL TERHADAP PERBUATAN I.IUKUIU PERSEROAN TERBATAS - Sufiariana Sufiariana (Jurnal ADIL, 2015)
Abstract A limited company which is run by owners, or inrlrviduels, reccivrslegal recognition from ltlinistry of Legai Affairs and Hurnan RiEhis.Prior to its legal recognition, a limiteC company ref*rs its iegalconsequeRces and obligations to the owners, Howevei., it is p*ssiblethat a limited company bears all of its legal cCIilseqlisnces andobligations provided that it fully accepts them. lndependent innature, this legal entity shares separate assets and cbligations withits owners. When the owners act in accordance with their authority,they can refer their consequences to this iegal eniity, if they don't,they will have to bear the legal consequences themselves,Keywords: Piercing the corporate veil, Limited Company